2016
DOI: 10.1021/acs.jpcc.6b00459
|View full text |Cite
|
Sign up to set email alerts
|

Unique Gold Nanorods Embedded Active Layer Enabling Strong Plasmonic Effect To Improve the Performance of Polymer Photovoltaic Devices

Abstract: It has been widely reported that plasmonic effects of metallic nanomaterials can enhance light-harvesting in polymer solar cells (PSCs). However, the improved light trapping degree is closely related to the shape of the nanoparticles (NPs), which inevitably limits the efficiency enhancement for PSCs. In this paper, we demonstrate that the incorporation of Au arrowhead nanorods (AHNRs) into the active layer of inverted PSCs can dramatically lead to a 28.7% efficiency enhancement as compared to preoptimize contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…As shown in Figure (a), the control device without added GNRs had a PCE of 7.43%, which is higher than those of P3HT‐ and PCDTBT‐based solar cells, similar to previous PTB7‐based studies. When increasing the amount of GNRs (from 0.15 to 0.45 wt %), the PCEs gradually improved from 7.74% to 8.22%, with the PCE improving by up to 11%.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…As shown in Figure (a), the control device without added GNRs had a PCE of 7.43%, which is higher than those of P3HT‐ and PCDTBT‐based solar cells, similar to previous PTB7‐based studies. When increasing the amount of GNRs (from 0.15 to 0.45 wt %), the PCEs gradually improved from 7.74% to 8.22%, with the PCE improving by up to 11%.…”
Section: Resultssupporting
confidence: 84%
“…The energy‐dispersive spectrometer spectrum shown in Supporting Information Figure S2 further confirmed that the GNRs were protected by DDT. The UV–vis spectrum of the GNRs showed two absorption peaks at wavelengths of 520 and 685 nm . The atomic force microscopy images in Figure (a,b) show that most GNRs were doped inside the PTB7/PC 70 BM layers.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The material, shape, size, concentration, composition and location of incorporated metal NPs are key parameters to tailor the resonant frequency and coupling efficiency of LSPR in OPVs. For example, Guo et al [126] reported the application of Au arrowhead nanorods (ARNRs) in the inverted polymer OPVs based on PCDTBT and PC 71 BM, and the PCE was improved from 5.75% to 7.40% with a maximum enhancement of 28.7%. Except for exciting the LSPR, the ARNRs in the active layers also reduced the cell resistance and improved the charge transport as demonstrated by the experimental and theoretical analyses.…”
Section: Lsprmentioning
confidence: 99%